The Dynamic Simulation of The Benzene and Toluene Distillation Process - Abdussalam Topandi; Khadijah Sayyidatun Nisa; Ibnu Maulana Hidayatulloh (Department of Chemical Engineering, Politeknik Negeri Bandung, 2023)
Benzene and toluene are products of petroleum catalytic fractionation and dehydrogenation, which are massively used for industrial purposes. The mixture of these two compounds forms an azeotropic condition that requires high energy and expensive investment. The separation process simulation is the appropriate way to address this problem. The technique of separating benzene and its derivatives from toluene is crucial if the product is to be reused for the following process. We propose a simulation of the separation of benzene and toluene using Aspen HYSYS with several assumptions (Peng-Robinson Fluid Package and Transfer Function Block) and operating conditions settings (pressure, flow rate, and vapor fraction). The simulation results were analyzed by comparing treatments without and with dynamic system settings (sudden and gradual changes in operational parameters for 30 minutes). The simulation results revealed that the stepwise dynamic system configuration might increase 10% extra moles of benzene. In addition, dynamic system settings also significantly affect the concentration of the bottom product.